Pruritus characteristics in a large Italian cohort of psoriatic patients. (15th April 2019) - Damiani, G.; Cazzaniga, S.; Conic, R.R.Z.; Naldi, L.; ,
Abstract: Background: Psoriasis (Ps) is a chronic systemic autoimmune disease associated with pruritus in 64–98% of patients. However, few modestly sized studies assess factors associated with psoriatic pruritus. Objective: To investigate factors associated with Ps pruritus intensity. Methods: Psoriasis patients 18 years or older seen in one of 155 centres in Italy between September 2005 and 2009 were identified from the Italian PsoCare registry. Patients without cutaneous psoriasis and those with missed information on pruritus were excluded. Results: We identified 10 802 patients, with a mean age 48.8 ± 14.3 years. Mild itch was present in 33.2% of patients, moderate in 34.4%, severe in 18.7% and very severe in 13.7%. Higher itch intensity was associated with female gender, lower educational attainment compared to university degree, pustular psoriasis, psoriasis on the head, face, palmoplantar areas, folds and genitalia, more severe disease, disease duration <15 years, and no or few prior systemic treatments. Limitations: Effects of specific medication on itch were not assessed. Conclusions: Pruritus should be evaluated during psoriasis visits, and physicians should be aware of patients at higher risk for itch. Further studies are needed to assess the effects of medications on itch, and establish therapy for psoriasis patients with persistent itch.